Trading on Talent: Human Capital and Firm Performance - Fedyk, Anastassia; Hodson, James (Review of Finance, 2023)
Abstract How is technically skilled human capital reflected in firm performance? We leverage a uniquely detailed employer–employee matched dataset to measure US firms’ technical human capital in information technology (IT), Software Engineering, Mobile Networks, Data Analysis, and Web Development. All five technical skillsets are associated with higher firm valuations. However, they negatively forecast both financial and operational performance in the future. For example, a one-standard-deviation increase in employees with IT skills corresponds to 2.2% higher Tobin’s q but predictable future returns of –10 basis points per month. Our results are stronger in tighter labor markets, in firms with more cash, and during time periods when each technical skillset is especially popular. These patterns suggest that the market expects too much from popular technologies, leading to over-valuation. Overall, our results highlight how corporate over-investment can extend to intangible capital such as skilled employees.